Synthesis of linear unsubstituted poly(4, 4′‐triphenylamine) via Suzuki‐Miyaura coupling of an asymmetric AB monomer. Issue 12 (11th May 2022) - Kao, Tzu‐Han; Qiao, Zhi; Ho, Po Yuen; Ditzer, Oliver; Sun, Ningwei; Voit, Brigitte; Lissel, Franziska
Abstract: Polytriarylamines (PTAAs) are amorphous polymers that can be reversibly oxidized to generate stable radical cations. Despite exhibiting a low charge carrier mobility, PTAAs are widely used as hole‐transporting layers in perovskite solar cells due to their excellent stability under ambient conditions. The highest occupied molecular orbital (HOMO) energy levels of PTAA are generally in the range of −5.1 to −5.2 eV, and therefore slightly too high for an optimal alignment with perovskites. Most linear PTAAs carry two or three methyl substituents per repeating unit. While these prevent crosslinking of chains and thus provide reaction control, the electron‐donating substituents raise the energy level of the HOMO. Unsubstituted PTAA on the other hand is usually obtained crosslinked via oxidative polymerization, while nickel‐catalyzed Grignard polycondensation leads to inclusion of impurities. We report the synthesis of linear unsubstituted PTAA using Suzuki‐Miyaura coupling of a novel asymmetric monomer, 4‐((4‐bromophenyl)(phenyl)amino)phenyl)boronic acid M1 . Based on matrix‐assisted laser desorption/ionization‐time of flight (MALDI‐TOF) and 1 H NMR analysis, we can conclude that the hydrogen‐terminated linear polymer is obtained. The determined HOMO energy level of −5.47 eV is a favorable match for many perovskite systems. Abstract :